1953
DOI: 10.1038/bjc.1953.20
|View full text |Cite
|
Sign up to set email alerts
|

The Hormonal Background of Ovarian Experimental Tumourigenesis in the Guinea-Pig

Abstract: THE tumours which appear in the intrasplenic ovarian graft in castrated rats, mice, guinea-pigs or rabbits apparently are due to the uncontrolled gonadotrophic activity of the prehypophysis, the ovarian steroid hormones which normally control hypophysial activity being inactivated during their passage through the liver before reaching the general circulation (Iglesias, Mardones and Lipschutz, 1953). The most striking proof in favour of this explanation is given by the administration of ovarian hormones. When o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1974
1974
1974
1974

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…These factors may be inter-related because low parity may be related to high income, certain cultural (ethnic) patterns, late marriage and urban residence. Experimental studies have also suggested the influence of pituitary hormones and direct gonadal factors in ovarian tumorogenesis (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The clinical, epidemiologic and experimental evidence thus far available therefore seems to suggest that total pregnancy experience is one of the most significant variables associated with ovarian cancer in women.…”
mentioning
confidence: 99%
“…These factors may be inter-related because low parity may be related to high income, certain cultural (ethnic) patterns, late marriage and urban residence. Experimental studies have also suggested the influence of pituitary hormones and direct gonadal factors in ovarian tumorogenesis (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The clinical, epidemiologic and experimental evidence thus far available therefore seems to suggest that total pregnancy experience is one of the most significant variables associated with ovarian cancer in women.…”
mentioning
confidence: 99%